Global dump toxic waste and the planetary ecosystem - Films For The Humanities & Sciences (Firm) (Hamilton, NJ : Films for the Humanities & Sciences, 2008)
Looks at the implications of the growing need for dumping grounds for the waste generated by the manufacture of new consumer goods and the discarding of old ones. Examines the globalization of industrial waste disposal, including toxic materials, and the shifting of the burden to less-developed nations in Asia, Africa, and Latin America. Also discusses the likelihood of more severe consequences of environmental change and degradation in the Third World
DVD format
Keywords: Hazardous wastes -- Developing countries; Environmental degradation -- Developing countries; Environmental policy -- Developed countries